Degraded land rehabilitation through agroforestry in India: Achievements, current understanding, and future prospectives - Jinger, Dinesh; Kaushal, Rajesh; Kumar, Raj; Paramesh, Venkatesh; Verma, Archana; Shukla, Monika; Chavan, Sangram Bhanudas; Kakade, Vijaysinha; Dobhal, Sneha; Uthappa, Appanderanda Ramani; Roy, Trisha; Singhal, Vibha; et al. (Frontiers in Ecology and Evolution, 2023)
Land degradation is one of the most important factors responsible for alarming situation of food security, human safety, and socioeconomic development in the country. Soil erosion caused by water and wind, physical, chemical and biological degradation are major form of land degradation in the country. Deforestation, intensive rainfall, uncontrolled grazing, indiscriminate use of agrochemicals, shifting cultivation are other major factors which further aggrevate the process of land degradadtion. In order to alleviate the problem of land degradation, numerous agroforestry technologies have been developed after years of research in different agroclimatic zones of the country. These technologies have been proven effective not only for rehabilitation of degraded lands, but have enough potential to address the issues of food, environmental and livelihood and security. The review article is an attempt to compile different kinds of agroforestry solutions for the rehabilitation of various types of degraded lands. This review's findings will benefit researchers, land managers, and decision-makers in understanding the role of agroforestry in combating land degradation in India and and planning suitable policies for eradicating the problem effectively.